The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4081/jlimnol.2018.1636
|View full text |Cite
|
Sign up to set email alerts
|

Multi-year succession of cyanobacteria blooms in a highland reservoir with changing nutrient status, Guizhou Province, China

Abstract: Over the last 22 years significant phytoplankton changes in Hongfeng lake reservoir have been observed with multiple years of harmful cyanobacteria blooms (cHABs). Fish farming and other anthropogenic activities from 1994-2001 triggered the harmful blooms. Nine years after the cessation of aquaculture, a conversion from problematic species (Microcystis spp, Aphanizomenon flos-aquae) to the less problematic species P. limnetica and other associated non-cyanobacteria taxa was recorded. Through this period of cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Microcystis spp. blooms for instance are favoured by higher temperatures, higher nutrient (TN, TP) contents, and reasonable light (Pick 2016;Long et al 2018), while Pseudanabaena limnetica is favoured by lower temperature (< 20°C) as observed during a monitoring in the Hongfeng Lake reservoir (Guizhou Province, China) (Long et al 2018). Moreover, Microcystis spp.…”
Section: Species Switch During the Cyanobacterial Bloom In Lake Tanga...mentioning
confidence: 94%
See 3 more Smart Citations
“…Microcystis spp. blooms for instance are favoured by higher temperatures, higher nutrient (TN, TP) contents, and reasonable light (Pick 2016;Long et al 2018), while Pseudanabaena limnetica is favoured by lower temperature (< 20°C) as observed during a monitoring in the Hongfeng Lake reservoir (Guizhou Province, China) (Long et al 2018). Moreover, Microcystis spp.…”
Section: Species Switch During the Cyanobacterial Bloom In Lake Tanga...mentioning
confidence: 94%
“…Strong SE trade winds in 2018 most likely induced a strong tilting of the thermocline and the Dolichospermum flosaquae bloom observed in September, just after the dry season winds, is likely the consequence of an upward movement of hypolimnion nutrient-rich water at this moment of the year as water layers oscillate to recover initial depths (Mortimer 1974;Plisnier et al 1999). Nutrient loading of anthropogenic impact or erosion are in this case not responsible for the Cocquyt et al, Phytoplankton bloom in Lake Tanganyika cyanobacteria bloom as often observed in aquatic ecosystems (Paerl & Huisman 2009;Long et al 2018). Rivers flowing into Lake Tanganyika are colder than the surface water of the lake and quickly sink into the hypolimnion (Capart 1949;Pierre-Denis Plisnier, pers.…”
Section: Secondary Upwelling In the North Of Lake Tanganyikamentioning
confidence: 98%
See 2 more Smart Citations
“…Dinoflagellates-based or diatoms blooms are not as harmful to citizens as cyanobacteriabased blooms, but their massive growth is as degrading to the freshwater quality and to the entire aquatic ecosystem as cyanobacteria blooms [3]. Additionally, Long et al [4] have reported a positive relationship between the biomass of phytoplankton as well as the concentration of their main pigment, Chlorophyll-a (chl_a), and the biomass of cyanobacteria. For these reasons, the World Health Organization (WHO) has listed chl_a as a mandatory parameter to measure in freshwater guidance level for cyanobacteriarelated risk (https://www.who.int/water_sanitation_health/bathing/srwe1-chap8.pdf, accessed on 4 February 2021).…”
Section: Introductionmentioning
confidence: 99%